HUBUNGAN TIMBAL DARAH TERHADAP KELAINAN SEL DARAH PADA ANAK JALANAN DI KOTA YOGYAKARTA - Hieronymus Rayi Prasetya (Meditory : The Journal of Medical Laboratory, 2021)
Introduction : Increasing ownership of motorized vehicles will be accompanied by increased use of fuel followed by high air pollution (lead). Pb can cause erythrocyte hemolysis and inhibit the formation of hemoglobin. This causes a decrease in the life span of erythrocytes and increases the fragility of erythrocyte membranes. Lead poisoning in the blood is characterized by basophilic stippling in erythocytes. Street musicians who do their work on the edge of the road (traffic light) are a group of populations that are susceptible to Pb poisoning, due to exposure to vehicle fumes every day as well as low knowledge about health conditions and the use of personal protective equipment (masks).Aims : This study aims to determine the effect of lead exposure on quantity (amount) and quality of blood cells (morphology).Method : The study was conducted by survey method, questionnaire and laboratory examination (blood lead, complete blood count, blood cell morphology). The data obtained were 32 samples analyzed using Spearman nonparametric with a confidence level of 95%.Results : The results of blood lead examination obtained 100% of respondents had normal lead levels (100 µg / L). The results also showed no association between blood lead with hemoglobin, erythrocytes, platelets, leukocytes, hematocrit, neutrophils, lymphocytes, monocytes, eosinophils, and basophils. Based on the results of morphological examination of erythrocytes, it shows that all respondents did not experience erythrocyte size, color and shape abnormalities and found no basophilic stippling.Conclutions : There is no relationship between blood lead and the quantity of blood cells. Morphological examination of blood cells found no cell abnormalities and found no basophilic stippling. Despite being exposed to vehicle fumes every day, respondents of street children did not experience lead poisoning and did not experience blood cell disorders.